2016
DOI: 10.1371/journal.pone.0166880
|View full text |Cite
|
Sign up to set email alerts
|

Visual Enhancement of Illusory Phenomenal Accents in Non-Isochronous Auditory Rhythms

Abstract: Musical rhythms encompass temporal patterns that often yield regular metrical accents (e.g., a beat). There have been mixed results regarding perception as a function of metrical saliency, namely, whether sensitivity to a deviant was greater in metrically stronger or weaker positions. Besides, effects of metrical position have not been examined in non-isochronous rhythms, or with respect to multisensory influences. This study was concerned with two main issues: (1) In non-isochronous auditory rhythms with clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…A third common human activity where isochrony is hypothesized to play a role is dance ( Fitch, 2016 ; Laland et al, 2016 ; Richter and Ostovar, 2016 ; Su, 2016a , b ). Similarly to music, a series of isochronous events, such as a drum line, may provide anchor points in time used to structure dance movements ( Fitch, 2016 ; Laland et al, 2016 ).…”
Section: The Relevance Of Isochrony To Human Music and Speechmentioning
confidence: 99%
“…A third common human activity where isochrony is hypothesized to play a role is dance ( Fitch, 2016 ; Laland et al, 2016 ; Richter and Ostovar, 2016 ; Su, 2016a , b ). Similarly to music, a series of isochronous events, such as a drum line, may provide anchor points in time used to structure dance movements ( Fitch, 2016 ; Laland et al, 2016 ).…”
Section: The Relevance Of Isochrony To Human Music and Speechmentioning
confidence: 99%
“…The field of musical rhythm is increasingly expanding to encompass the scientific study of dance (Ellamil et al, 2016 ; Fink and Shackelford, 2017 ; Fitch, 2016 ; Laland et al, 2016 ; Ravignani and Cook, 2016 ; Su, 2016 ). Only in 2016, three papers have introduced conceptual frameworks for the evolutionary study of dance (Fitch, 2016 ; Laland et al, 2016 ; Ravignani and Cook, 2016 ).…”
Section: Rhythm In Other Journals Since Late 2015mentioning
confidence: 99%
“…Given these connections, surprisingly little is known about how the rhythms of music and dance interact in perception when experienced simultaneously. A few recent studies have suggested that, when presented concurrently in a synchronized manner, the visual rhythm of a street-dance-like bouncing movement can facilitate auditory beat perception (Su, 2014b) and that of a swing dance repertoire can impose metrical accents on auditory rhythms (Su, 2016b). Although these findings demonstrate visual modulation of auditory rhythm perception, it remains unclear what influences cross-modal binding between musical and dance rhythms, a question the present investigation was intended to address.…”
mentioning
confidence: 84%